Peripartum Cardiogenic Shock and Mechanical Circulatory Support - Giulia Botti; Sharmaine Thirunavukarasu; Francesca Ziviello; Alaide Chieffo (Interventional Cardiology: Reviews, Research, Resources)
Despite remarkable improvements in the past two decades, the annual cardiovascular mortality rate has remained higher for women than for men. Pregnant women represent an underinvestigated population in clinical research, and the mechanisms of long-term cardiovascular complications in women with obstetric complications remain to be elucidated. Regarding advanced heart failure during pregnancy, interventional approaches are effective but still underutilised. Percutaneous mechanical circulatory support is a valuable option for peripartum cardiogenic shock, although its use during pregnancy is still limited. Survival rates have improved in recent years, but further emphasis on the importance of early recognition and initiation of heart failure treatment in this patient group is warranted. The aims of this review are to summarise the current literature on the implementation of mechanical circulatory support in cardiogenic shock during pregnancy and delivery and to understand the role of percutaneous ventricular assist devices in the management of such conditions.